Digital doctorates? An exploratory study of PhD candidates' use of online tools. Issue 1 (2nd January 2017) - Dowling, Robyn; Wilson, Michael
Abstract : Online environments are transforming learning, including doctoral education. Yet the ways in which the PhD experience is shaped and transformed through these digital modes of engagement is seldom addressed, and not systematically understood. In this article, we explore PhD students' perceptions and use of digital tools. Drawing on the results of focus groups with PhD candidates at a metropolitan Australian university, we argue that PhD candidates' appropriation and use of online resources and tools are growing but at the same time remains overlain by traditional concerns of time and convenience, technological expertise, established channels of communication and preferred services. We conclude that PhD candidates' use of online tools is not so much a question of skill proficiency as it is about the tools' immediate utility in relation to candidates' time-pressured and habitual ways of researching.